Virtual organization support through electronic institutions and normative multi-agent systems - Henrique Lopes Cardoso (2006)
The multi-agent system (MAS) paradigm has become a prominent approach in distributed artificial intelligence. Many real-world applications of MAS require ensuring cooperative outcomes in scenarios populated with self-interested agents. Following this concern, a strong research emphasis has been given recently to normative MAS. A major application area of MAS technology is e-business automation, including the establishment and operation of business relationships and the formation of virtual organizations (VOs). One of the key factors influencing the adoption of agent-based approaches in real-world business scenarios is trust. The concept of an electronic institution (EI) has been proposed as a means to provide a regulated and trustable environment, by enforcing norms of behavior and by providing specific services for smooth inter-operability. This chapter exposes our work towards the development of an agent-based EI providing a virtual normative environment that assists and regulates the creation and operation of VOs through contract-related services. It includes a presentation of the EI framework, knowledge representation structures for norms in contracts, and a description of two main institutional services, namely negotiation mediation and contract monitoring.